2019
DOI: 10.2174/1389450120666190715104100
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Exosomes: Steps Towards Green Production of Drug Delivery System

Abstract: Targeting of therapeutic agents to their specific site of action not only increases the treatment efficacy, but also reduces systemic toxicity. Therefore, various drug delivery systems (DDSs) have been developed to achieve this target. However, most of those DDSs have several issues regarding biocompatibility and environmental hazard. In contrast to the synthetic DDSs, exosome-based natural carriers are biocompatible, biodegradable and safe for the environment. Since exosomes play a role in intercellular commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 108 publications
0
18
0
Order By: Relevance
“…Therefore, it could be concluded that GEF-P-NLC produces cytotoxic activity through the aforementioned mechanism. This not only increases the efficacy of therapeutic outcomes but also decreases the toxicity of GEF by decreasing the required dose [49]. Taken all together, TPGS engineered nanoscale lipid-based LDDS is expected to increase the therapeutic outcomes of GEF during the treatment of metastatic lung cancer.…”
Section: Apoptotic Studymentioning
confidence: 98%
“…Therefore, it could be concluded that GEF-P-NLC produces cytotoxic activity through the aforementioned mechanism. This not only increases the efficacy of therapeutic outcomes but also decreases the toxicity of GEF by decreasing the required dose [49]. Taken all together, TPGS engineered nanoscale lipid-based LDDS is expected to increase the therapeutic outcomes of GEF during the treatment of metastatic lung cancer.…”
Section: Apoptotic Studymentioning
confidence: 98%
“…The advantage is that RBCs can effectively target the reticuloendothelial system. And the release of the drug and the maintenance of the plasma drug concentration can be controlled ( Sherif et al, 2019 ). However, cells as drug transport carriers still face many problems, such as uncertain cell differentiation, cell embolism, infection, and difficulties in production and storage.…”
Section: Production Process Of Exosomesmentioning
confidence: 99%
“…For efficient drug delivery, drugs can firstly be ingested into cell. Then, these drugs will be load into sEVs with the formation process of sEVs [ 128 ]. Ingesting specific drug can sometimes stimulate donor cells to produce other therapeutic substances which will be packed into sEVs [ 84 , 86 ].…”
Section: Applications Of Modulated Sevs In Disease Treatmentsmentioning
confidence: 99%